Advances in Experimental Markets - Cason, Timothy; Noussair, Charles (Springer Berlin Heidelberg, 2001)
Experimental methods are now a mainstream empirical methodology in economics. The papers in this volume represent some recent developments in research on experimental markets. The articles span a variety of topics related to experimental markets, including auctions, taxation, institutional differences, coordination in markets, and learning. Contributors to the volume include many of the most distinguished researchers in the area
Keywords: Economic Theory/Quantitative Economics/Mathematical Methods; Quantitative Finance; Economic theory; Economics, Mathematical; Experiment; Methode; Ökonometrie; Marktverhalten; Experimentelle Spieltheorie; Aufsatzsammlung